lncRNA TUG1 promotes proliferation and differentiation of osteoblasts by regulating the miR-545-3p/CNR2 axis - Hao,Ruizheng (2020)
Osteoblast differentiation is an effective way to promote bone formation. Long non-coding RNA taurine upregulated 1 (TUG1) has been identified as a crucial modulator of multiple biological processes. This study was designed to investigate the function of TUG1 in the proliferation and differentiation of osteoblast precursor cells hFOB1.19. In this study, we found that TUG1 promoted hFOB1.19 cell proliferation, while TUG1 knockdown hindered cell proliferation. TUG1 and cannabinoid receptor 2 (CNR2) were upregulated, while miR-545-3p was down-regulated in hFOB1.19 cells undergoing osteoblastic differentiation. TUG1 induced osteoblast differentiation by increasing alkaline phosphatase (ALP) activity and the expression of osteoblastic differentiation markers. TUG1 was a sponge of miR-545-3p and regulated osteoblastic differentiation by modulating miR-545-3p. Moreover, miR-545-3p directly targeted CNR2 and restored the effect of CNR2 on osteoblastic differentiation. In conclusion, TUG1 accelerated the proliferation and differentiation of osteoblasts by sponging miR-545-3p and increasing CNR2 expression, which might provide a new biomarker for bone diseases.